FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI PRODUK HIJAU DIKALANGAN MAHASISWA - Robbani, M. Habiburrohman; Soepatini, Soepatini (ITB AAS Indonesia Surakarta, 2024)
This research aims to analyze the factors that influence interest in buying green products among students. Attitudes towards green products serve as an intermediary variable in this study, which primarily focuses on product knowledge, consumer perceived effectiveness, and purchase intention. In this quantitative study, which will take place in Indonesia on May 2, 2024, data will be collected from all interested and participating students using a questionnaire. The researchers in this study used the Partial Least Square (PLS) algorithm to conduct their quantitative analysis. The results of the SmartPLS 3.0 analysis demonstrate the following relationships: (1) attitudes are positively affected by product knowledge; (2) attitudes towards green products are positively affected by perceived consumer effectiveness; (3) purchase intention is positively affected by perceived product knowledge; (4) purchasing interest is positively affected by perceived consumer effectiveness; (5) attitudes towards green products are positively affected by purchase intention; (6) product knowledge is positively affected by purchase intention through attitudes towards green products; (7) perceived consumer effectiveness is positively affected by purchase intention through attitudes towards green products.